A field camera for MR sequence monitoring and system analysis. Issue 4 (14th May 2015) - Dietrich, Benjamin E.; Brunner, David O.; Wilm, Bertram J.; Barmet, Christoph; Gross, Simon; Kasper, Lars; Haeberlin, Maximilian; Schmid, Thomas; Vannesjo, S. Johanna; Pruessmann, Klaas P.
Abstract : Purpose: MR image formation and interpretation relies on highly accurate dynamic magnetic fields of high fidelity. A range of mechanisms still limit magnetic field fidelity, including magnet drifts, eddy currents, and finite linearity and stability of power amplifiers used to drive gradient and shim coils. Addressing remaining errors by means of hardware, sequence, or signal processing optimizations, calls for immediate observation by magnetic field monitoring. The present work presents a stand‐alone monitoring system delivering insight into such field imperfections for MR sequence and system analysis. Methods: A flexible NMR field probe‐based stand‐alone monitoring system, built on a software‐defined‐radio approach, is introduced and used to sense field dynamics up to third‐order in space in a selection of situations with different time scales. Results: Highly sensitive trajectories are measured and successfully used for image reconstruction. Further field perturbations due to mechanical oscillations and thermal field drifts following demanding gradient use and external interferences are studied. Conclusion: A flexible and versatile monitoring system is presented, delivering camera‐like access to otherwise hardly accessible field dynamics with nanotesla resolution. Its stand‐alone nature enables field analysis even during unknown MR system states.Magn Reson Med 75:1831–1840, 2016. © 2015 Wiley Periodicals, Inc.